DESCRIPTION ON THE MEGALITHIC TRADITION OF INDONESIA - Haris Sukendar (Berkala Arkeologi, 1987)
Megalithic remains are widely distributed over nearly all the regions of Indonesia, among others in Sumatra, Nias, Java, Bali, Sulawesi, Sumba, Sumbawa, Aores, Sabu etc. There are various forms of megalithic remains which have their own characteristics in certain areas. For instance, the megalithic remains in Nias are known as osa-osa (seats) and dane-dane (tables). Lampung is known for its dolmen. In West Java the stepped terrace are wellknown, while there are kalamba in Central Sulawesi and sarcophagi in Bali. Megalithic remains exhibit wider range of forms as more and more are discovered in various parts of Indonesia.